Comparison of Airborne Bacterial Populations Determined by Passive and Active Air Sampling at puy de Dôme, France - Kevin P. Dillon; Romie Tignat-Perrier; Muriel Joly; Sydonia N. C. M. Grogan; Catherine Larose; Pierre Amato; Gediminas Mainelis (Aerosol and Air Quality Research)
Abstract Bioaerosols have impacts on atmospheric processes, as well as ecosystem and human health. Common bioaerosol collection methods include impaction, liquid impingement, filtration, and electrostatic precipitation. These methods are used by active samplers that require an air mover and power, but this requirement can also represent a major constraint in field studies. Alternatively, passive samplers do not require power and can operate for long times. In this study, the Rutgers Electrostatic Passive Sampler (REPS), which captures particles by electrostatic attraction and gravitational settling, was deployed at the summit of puy de Dôme (1465 m a.s.l., France) alongside an active PM10 sampler (~1000 L min−1) collecting aerosols on a quartz fiber filter. The diversity of the airborne bacteria captured by both samplers across six weekly sampling periods was examined by 16S rRNA gene amplicon sequencing. The dominant phyla observed by both samplers were similar and included Firmicutes, Proteobacteria, and Actinobacteriota. Overall, 12 to 63% of the total bacterial richness at the genus level was shared between the two samplers, depending upon a paired sample, i.e., sampling week. The PM10 sampler and REPS detected the same dominant genera, including Lysinibacillus and Sphingomonas, although their relative abundances for each paired sampler varied. The observed bacterial richness and diversity, as estimated through Shannon’s and Simpson’s indexes, were significantly greater in REPS samples compared to the PM10 samples. The results suggest that REPS could be used for simple and convenient sampling of bioaerosols, especially in remote areas and other locations with limited power access.